Fracture resistance of molars with class II MOD cavities restored with bulk-fill, no-cap flowable bulk-fill, and conventional resin composite restorative systems after 6-months water storage - Ramy Ahmed Wafaie; Basma Ahmed; Salah Hasab Mahmoud (BMC Oral Health)
Abstract Background Bulk-fill resin composites are innovative materials, developed to simplify the placement of direct composite restorations especially in large cavities. Recently, a new class of flowable bulk-fill resin composite is claimed to be placed without final capping layer. Thus, this study aimed to assess and compare the fracture resistance of molars with Class II MOD cavities restored with different types of resin composite restorative systems after 6-month water storage. Methods One-hundred sound mandibular molars were assigned randomly into 5 groups (n = 20). The teeth in the first group were left intact and tested as unprepared positive control (group I), while teeth in the remaining four groups received Class II MOD cavities. One of the prepared groups was left unrestored and tested as negative control (group II). The remaining three groups were restored as follows; group III: bulk-fill resin composite/Filtek One Bulk Fill (3 M Oral Care), group IV: no-cap flowable bulk-fill resin composite/G-aenial bulk injectable (GC), and conventional resin composite/Neo Spectra ST LV (Dentsply Sirona). Half of the specimens of each group (n = 10) was stored in distilled water at 37 °C for 24 h and then thermocycled 5000 times between 5 °C ± 2 °C and 55 °C ± 2 °C (immediate), while the other half was stored for 6 months before thermocycling (delayed). All specimens were loaded occlusally in a universal testing machine using a metal sphere that contacted the teeth at the cuspal inclines until fracture occurred. The results were analyzed by 2-way ANOVA and Tukey HSD post-hoc multiple comparison tests. The level of significance was set at p < 0.05. Results Regardless of storage time, intact molar teeth showed significantly higher fracture resistance mean values than did the other tested groups (p < 0.05). The groups restored with bulk-fill and conventional resin composites showed higher mean values compared to the group restored with no-cap flowable bulk-fill resin composite (p < 0.05). The prepared unrestored group exhibited the lowest fracture resistance mean values (p < 0.05). Statistically significant differences were observed when comparing immediate and delayed restored groups (p < 0.05). Conclusions The fracture resistance of Class II MOD cavities restored with bulk-fill or conventional resin composites was superior to those restored with no-cap flowable bulk-fill resin composite. Moreover, 6-month water storage had a deleterious effect on the fracture resistance of the restored molar teeth.